Situation Report: Hungary, 21 November 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Clues about Kadar's Whereabouts before 4 November 1956 / by Alfred Reisch Will the New Family Law Serve Its Purpose? / by Judith Pataki Hungarian Minority's Rights in Romania Raised Again / by Alfred Reisch Soviet Economists Discuss Economic Reform in the USSR / by Alfred Reisch Hungary Complains about CMEA Electricity Supplies / by Karoly Okolicsanyi